2014
DOI: 10.1111/jir.12126
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perceptions of sibling adaptation in Korean families of children with Down syndrome

Abstract: These findings highlight the importance of familial contexts in understanding sibling adaptation. Knowledge of family factors associated with better adaptation in Korean siblings of child with DS will facilitate the development of culturally appropriate interventions for these children and their families. In addition, an awareness of demographic characteristics associated with sibling adaptation will help health care professionals identify siblings who are at increased risk of experiencing difficulties in adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 48 publications
0
33
1
1
Order By: Relevance
“…Only four studies identified their guiding framework; two used family frameworks, the Resiliency model (Hsiao & Van Riper , Choi & Van Riper ) and Patterson's family resilience model (Choi & Yoo ) and one used an individual‐centric framework, the stress and coping model (Lam & Mackenzie ). Two studies were comparative (Cheng & Tang , Gau et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only four studies identified their guiding framework; two used family frameworks, the Resiliency model (Hsiao & Van Riper , Choi & Van Riper ) and Patterson's family resilience model (Choi & Yoo ) and one used an individual‐centric framework, the stress and coping model (Lam & Mackenzie ). Two studies were comparative (Cheng & Tang , Gau et al .…”
Section: Resultsmentioning
confidence: 99%
“…While only one level of adaptation was assessed in most studies, (Cheng & Tang , Choi et al . , Choi & Van Riper , Hsiao ), two levels were assessed in two studies (Hsiao & Van Riper , Choi & Yoo ) and all three levels (individual, dyadic and family) were assessed in two studies (Chiu et al . , Gau et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudos mostram ainda que o bem-estar do irmão com DT pode ser muito influenciado pelos seguintes fatores: as exigências e os desafios que estão associados aos cuidados de uma criança com SD (demandas familiares), a percepção da família acerca do filho com SD (avaliação da família), a forma como a família lida com as dificuldades (estratégias familiares de resolução de problemas e de enfrentamento) e os recursos disponíveis à família (Choi, & Van Riper, 2014). Nesse sentido, há diferentes variáveis/fatores que se inter-relacionam e que têm implicações na dinâmica e funcionamento familiar e, consequentemente, nas relações fraternais, embora as pesquisas ainda mostrem resultados inconsistentes.…”
Section: Introductionunclassified